Expert consensus on the management of acne in India - Kandhari, Sanjiv; Girdhar, Mukesh; Kulkarni, Dipak S.; Arsiwala, Shehnaz; Sakhiya, Jagdish; Karthikeyan, K.; Murthy, Srinivas; Dhawan, Sachin; Mallela, Vijaya Bhaskar; Rathi, Sanjay (International Journal of Research in Medical Sciences, 2022)
Acne, a common cutaneous disorder, is estimated to affect a significant proportion of the population at some point in their lifetime. It is one of the most common presentations reported in dermatological consultations in India. Treatment options for acne include topical, oral and procedural therapies. Patients with mild acne can be treated with topical therapies; however, those with moderate to severe acne require systemic cure. Oral antibiotic treatment, hormonal therapies and isotretinoin are the mainstay systemic therapies for acne. Additionally, procedural therapeutic modalities in dermatology include chemical peels, laser therapy, micro needling techniques, to name a few. Scientific advances are continually improving knowledge of acne and contributing to refinement of treatment options. Hence, it is vital for clinicians to regularly update their clinical practice patterns to reflect current standard. An experts’ panel discussion involving dermatologists from across India was conducted, to outline a practical approach for the management of acne. The present consensus document focuses on the assessment of acne, use of topical treatments, role of systemic therapy and procedures in treating acne and post-inflammatory hyperpigmentation. It also emphasizes the role of patient education and counselling on prophylactic and treatment strategies in acne management.